MANAGEMENT STYLE OF HOSPITALITY AND TOURISM INSTITUTE (A CASE STUDY OF THE INTERNATIONAL BALI TOURISM INSTITUTE OF DENPASAR)e - Ni Made Ayu Sulasmini (Institut Pariwisata dan Bisnis Internasional, 2016)
Understanding management style enables managers to recognize their strength and weakness. This recognition allows an arrangement of a precise development management program; this will boost management performances that should be a support in developing the quality of a school. This study aimed to assess the management style of the International Bali Tourism Institute (STPBI). STPBI is a school that offers a diploma program for the hospitality and tourism students. A self-assessment management style instrument (DiPadova, 1990 in Petrick and Quinn, 1997) was used. The study indicates that in average, the managers in STPBI are strong in the role of director, but very weak in the role of broker. The result of this research depicts the management of STPBI should focus on developing the broker and producer areas to enable a well-rounded management style.